Synthesis and Luminescent Properties of a Novel Green-Emitting Iridium Complex (Journal of Atomic and Molecular Sciences, 2014)
A novel cyclometalated iridium complex bis[(4-(2-(4-Diphenylamino-phenyl)-benzoinidazol-1-ylmethyl)-phenyl)-diphenyl-amine]iridium(acetylacetonate) Ir(DBPA)$_2$(acac) is designed and synthesized, and the thermo-stability and photo-physicalproperties of iridium complex Ir(DBPA)$_2$(acac) are researched in detail. The complex isfunctionalized by a bulky non-planarity substituent, thus the phosphorescent concentrationquenching in solid state is substantially suppressed, and Ir(DBPA)$_2$(acac) exhibitsbright green-emitting in both solution and solid. The maximum emission peakinr pure solid is about 516 nm, which is slightly blue-shifted in comparison with that insolution. Moreover, the complex Ir(DBPA)$_2$(acac) exhibits high photoluminescent efficiencyand short excited lifetime, indicating it has potential application in fabricatingnodoped electrophosphorescence device.